GenomeFlow: a comprehensive graphical tool for modeling and analyzing 3D genome structure - Trieu, Tuan (Bioinformatics, 2019)
MOTIVATION: Three-dimensional (3D) genome organization plays important functional roles in cells. User-friendly tools for reconstructing 3D genome models from chromosomal conformation capturing data and analyzing them are needed for the study of 3D genome organization. RESULTS: We built a comprehensive graphical tool (GenomeFlow) to facilitate the entire process of modeling and analysis of 3D genome organization. This process includes the mapping of Hi-C data to one-dimensional (1D) reference genomes, the generation, normalization and visualization of two-dimensional (2D) chromosomal contact maps, the reconstruction and the visualization of the 3D models of chromosome and genome, the analysis of 3D models and the integration of these models with functional genomics data. This graphical tool is the first of its kind in reconstructing, storing, analyzing and annotating 3D genome models. It can reconstruct 3D genome models from Hi-C data and visualize them in real-time. This tool also allows users to overlay gene annotation, gene expression data and genome methylation data on top of 3D genome models. AVAILABILITY AND IMPLEMENTATION: The source code and user manual: https://github.com/jianlin-cheng/GenomeFlow. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.